(untitled) (Ius Novum, 2025)
The article addresses the issue of discontinuation of proceedings due to the health condition of the accused that permanently prevents them from participating in the proceedings – based on the provision laid down in Article 17 § 1 subsection 11 of the Code of Criminal Procedure (CCP) – as a circumstance precluding prosecution. The research thesis is that the health condition of the accused may constitute grounds for discontinuing proceedings under this provision. A dogmatic legal approach and case law analysis are used to examine the issue. The doctrine and case law allow for this possibility, recognising that the poor health of the accused, due to its permanent nature, precludes the issuance of another substantive ruling concluding the proceedings. In opposition to this view, it is argued that the health condition of the accused may represent a factual obstacle preventing the conduct of proceedings and therefore provides grounds for their suspension (Article 22 § 1 CCP). Due to the strong polarisation of views on this issue, and the almost uniform case law of the Supreme Court, which holds that the health condition of the accused constitutes grounds for suspending proceedings, it is necessary for the legislature to intervene and add subsection 10a to Article 17 § 1 CCP, listing circumstances precluding prosecution, to include the health condition of the accused that permanently prevents participation in the proceedings.